Invisible Identity in the Workplace: Intersectional Madness and Processes of Disclosure at Work - Pilling, Merrick Daniel (Disability Studies Quarterly, 2012)
In this article I draw on recent work regarding disabilities that are not readily apparent to analyze the experiences of lesbian, gay, bisexual, queer, and/or trans (LGBQT) mad people in the workplace. Based on interviews with LGBQT people about madness and everyday life, I use an intersectional approach to examine participants’ work lives. I argue that decisions about disclosure of mental health related information are particularly pressing and high risk at work, given the economic stakes and the effects on health and well-being. As is the case for others with invisible disabilities, notions of authenticity shape processes of disclosure and access to accommodations for LGBQT mad people in the workplace. An intersectional analysis shows how madness cannot be considered the only salient aspect of my participants’ subject positions and how multiple identities operate together to shape their experiences. Keywords: madness, invisible disability, LGBQT, intersectionality, workplace, race, sexuality, gender identity